WHEY PROPERTIES AND ITS USE FOR PRODUCTION OF FUNCTIONAL AND PROBIOTIC DRINKS - Kalevska, Tatjana; Uzunoska, Zora; Stamatovska, Viktorija; Saveski, Aleksandar (Trakia University, 2018)
Whey is a by-product in the process of cheese production, represented with 85-90% from the total milk volume and contains 50% of the milk’s dry matter: lactose, whey proteins, minerals and vitamins. The high quality whey proteins are a source of energy and nutrients, rich with essential amino acids which makes them biologically essential proteins. The healing properties of whey are due to the presence of immunoglobulin and immunologically active substances which strengthen the immune system, protect the organism from different bacterial infections and allergic reactions. Only a small part of the whey produced in dairies in Macedonia is used for the production of albumin cheese, while the rest is left unused. The goal of this work is to show the therapeutic and functional properties of whey as well as the possibility of its use in production of functional and probiotic whey based drinks, with the use of new innovative technologies and scientific findings.